2021
DOI: 10.3758/s13423-020-01858-w
|View full text |Cite
|
Sign up to set email alerts
|

Through the eyes of the expert: Evaluating holistic processing in architects through gaze-contingent viewing

Abstract: Studies in the psychology of visual expertise have tended to focus on a limited set of expert domains, such as radiology and athletics. Conclusions drawn from these data indicate that experts use parafoveal vision to process images holistically. In this study, we examined a novel, as-of-yet-unstudied class of visual experts-architects-expecting similar results. However, the results indicate that architects, though visual experts, may not employ the holistic processing strategy observed in their previously stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…As with intelligent control for skill, there are likely many varieties of creativity that abide different degrees of automaticity and spontaneity. Carruthers (2011), for instance, suggests a 'constrained stochasticity' model of creativity which has it that in cases like improvisation (Berliner, 1994;Owens, 1995;Sudnow and Dreyfus, 2001;Baird, 2012) and spontaneous reaction (Runswick et al 2018;Ivy et al, 2021), creative events are "action-first," or represented in action prior to being representationally encoded by conscious thought. The actionfirst model has it that experts direct their course of action with a degree of stochasticity constrained by some rule or principle which serves to limit the stochastic nexus of possible actions to probably successful ones.…”
Section: Finding a Place For Creativity In Skillmentioning
confidence: 99%
“…As with intelligent control for skill, there are likely many varieties of creativity that abide different degrees of automaticity and spontaneity. Carruthers (2011), for instance, suggests a 'constrained stochasticity' model of creativity which has it that in cases like improvisation (Berliner, 1994;Owens, 1995;Sudnow and Dreyfus, 2001;Baird, 2012) and spontaneous reaction (Runswick et al 2018;Ivy et al, 2021), creative events are "action-first," or represented in action prior to being representationally encoded by conscious thought. The actionfirst model has it that experts direct their course of action with a degree of stochasticity constrained by some rule or principle which serves to limit the stochastic nexus of possible actions to probably successful ones.…”
Section: Finding a Place For Creativity In Skillmentioning
confidence: 99%
“…Our prior work suggested that HVP, as a marker of visual expertise, was not present in the behaviors of architect subjects 24 . Yet, lacking further data, we were unable to determine why this was the case.…”
Section: Discussionmentioning
confidence: 76%
“…Architects (n=27, 7 female, and 20 male) held either master’s degree or a license to practice architecture. The data from the naïve and architect groups has been previously published in an original study 24 . The average age of architects was 42 (SD=11.63) who collectively averaged 19 years of experience (SD=12.12).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations